The Simple View of Reading as a cognitive framework for multilingual reading comprehension assessment - Fethi, Naila; Józsa, Krisztián (Frontiers in Education, 2026)
Reading is an essential skill that shapes success in both academic and everyday life. However, assessing how well students understand written materials remains a complex task, particularly in multilingual contexts, where different languages interact. Therefore, this mini-review aims to explore relevant studies and highlight the potential of the Simple View of Reading (SVR) as a clear and practical cognitive vertex for developing reliable reading comprehension assessments across languages. This mini-review is based on structured searches in Scopus, Web of Science, and ERIC using key terms related to the SVR, decoding, language comprehension, and multilingual reading, and the retrieved studies were synthesized thematically. The main strength of the SVR lies in its simple and well-defined framework that makes it adaptable to diverse orthographies and contexts. Grounding assessment design in the SVR enables cross-language comparison, exploring the simultaneous development of literacy skills in multilinguals. It also identifies sources of reading difficulty, as decoding and language comprehension are measured separately to guide diagnosis and instruction. Moreover, it supports practical use in the classroom, using simple and low-cost assessment tools that allow teachers to obtain useful reading comprehension profiles for their students despite limited time and resources.